Image guided needle aspiration - a Sri Lankan experience - Kumarasinghe, M.P.; Lokuhetty, M.D.L; Perera, U.C.; Senanayake, G (My University, 1996)
Objectives: 1. To study the feasibility of using image guided FNAB in the diagnosis of deep-seated mass lesions in a Sri Lankan setting. 2. To assess the success rate of the technique and identify ways of improvement. Design: A joint study done by the Department of Pathology, Faculty of Medicine, Colombo and Department of Radiology , National Hospital of Sri Lanka over a period of 54 months, from January 1991. Materials and methods: All images guided FNABs jointly performed by the 2 teams were included and analysed according to the site and diagnosis. Follow-up was done comparing the histologic diagnosis and clinical outcome. Results: A total of 150 cases were analysed in lung, liver, pancreas, mediastinum, kidney, pleura and other organs. The only significant complication was a pneumothorax in one patient which needed an intercostal tube. One hundred and twenty eight aspirates were adequate. Therefore 85 percent were technically successful. A definite diagnosis was made in 116 of the 128(91percent). Seventy five were malignant (65 percent) and 41 benign (35 percent). Of the 29 with the follow-up in 27 the diagnosis was correct; 2 were false negatives. The diagnostic accuracy was 93 percent. Conclusions: Image guided FNAB can be used to investigate deep seated mass lesions in Sri Lanka. The technical success rate and accuracy were satisfactory. Success of the technique can be more if back up facilities including those of the laboratory can be improved.